Estimation of the lifespan distribution of gold nanoparticles stabilized with lipoic acid by accelerated degradation tests and wiener process - Cornejo Monroy, Delfino (2022)
Accelerated degradation tests (ADT) are widely used in the manufacturing industry to obtain information on the reliability of components and materials, by degrading the lifespan of the product by applying an acceleration factor that damage to the material. The main objective is to obtain fast information which is modeled to estimate the characteristics of the material life under normal conditions of use and to save time and expenses. The purpose of this work is to estimate the lifespan distribution of gold nanoparticles stabilized with lipoic acid (GNPs@LA) through accelerated degradation tests applying sodium chloride (NaCl) as an acceleration factor. For this, the synthesis of GNPs@LA was carried out, a constant stress ADT (CSADT) was applied, and the non-linear Wiener process was proposed with random effects, error measures, and different covariability for the adjustment of the degradation signals. The information obtained with the test and analysis allows us to obtain the life distribution in GNPs@LA, the results make it possible to determine the guaranteed time for possible commercialization and successful application based on the stability of the material. In addition, for the evaluation and selection of the model, the Akaike and Bootstrapping criteria were used.